(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
This article analyzes the issue of the tragic fate of female characters in the works of Alisher Navoi from artistic-aesthetic and socio-philosophical perspectives. In the poet’s oeuvre, the image of woman is not limited to a symbol of love and beauty; rather, it is portrayed against the background of complex social relations, societal pressure, and moral contradictions. The study demonstrates that the primary causes of female tragedy in Navoi’s epics include the patriarchal social environment, the restriction of women’s choices, and society’s denial of spiritual values. The article argues that tragedy is not the result of a woman’s personal fault, but a consequence of social injustice. The findings show that Navoi’s aesthetic views constitute an important theoretical source for studying contemporary literary issues related to women’s fate.